Venom proteomics, toxicity and cross-neutralization of samar cobra (Naja samarensis) from the Southern Philippines - Praneetha Palasuberniam (2022)
Snakebite envenoming by Naja samarensis, a medically important species endemic to the southern Philippines, results in neuromuscular paralysis and death from respiratory failure. Antivenom is the definitive treatment, but there is currently no species-specific antivenom for N. samarensis. Instead, Philippine Cobra Antivenom (PCAV), raised against Naja philippinensis (Philippine Cobra endemic to the northern Philippines), is used empirically to treat envenoming by N. samarensis in the south. Yet, the composition and toxicity of N. samarensis venom, physicochemical properties, and cross-neutralization capacity of PCA V against N. samarensis venom remain understudied. Hence, the present study investigated the venom proteome of N. samarensis through reverse-phase high-performance liquid chromatography, sodium dodecyl sulfatepolyacrylamide gel electrophoresis (SDS-PAGE), and tandem mass spectrometry (LCMS/ MS). The immunological binding activity of PCA V to N. samarensis venom and its protein components was examined with indirect enzyme-linked immunosorbent assay (ELISA) and immunoblotting. The toxicity and neutralization of N. samarensis venom and its principal lethal component, i.e., short-chain alpha-neurotoxin (Sa.NTX) using PCA V, were subsequently investigated in mice. The protein composition of PCA V was then examined using size-exclusion chromatography, SDS-PAGE and LC-MS/MS. The study further assessed the immunoreactivity of PCA V, containing antibodies primarily targeting SaNTX, against venoms of various cobra species, phylogenetically related cobra-like snakes (Hemachatus haemachatus, Aspidelaps scutatus, and Walterinnesia aegyptia), and alpha-neurotoxins from selected elapid species. The study identified 31 distinct proteofom1s from seven toxin families in the venom proteome of N. samarensis. Ill The three-finger toxin family are the most dominant components ( comprising ~90% of total venom proteins), with SaNTX being the primary constituent (74.2%). Other proteins identified were snake venom metalloproteinases, phospholipases A2, cysteine-rich secretory proteins, venom nerve growth factor, L-amino acid oxidase and vespryn. In ELISA, PCA V demonstrated comparable immunoreactivity toward the venoms of N. samarensis and N. philippinensis, based on its half-maximum effective concentrations of binding (ECso), 1.22 and 1.63 μg/ml, respectively (p>0.05). Immunoblotting showed that PCA V was able to bind strongly to the venom proteins, including toxins with low molecular mass (<10 kDa). This was further supported by PCAV immunorecognition of N. samarensis venom fractions containing the lethal SaNTX. N. samarensis venom was highly lethal to mice (intravenous median lethal dose, LDso=0.20 μg/g), attributed to the abundant SaNTX (LDso=0.18 μgig) in its venom. PCAV was able to cross-neutralize the toxicity of N. samarensis venom and its SaNTX in viva with moderate efficacy (neutralization potency=0.17 mg/ml and 0.20 mg/ml, respectively). Physicochemical profiling of PCAV revealed that it is a F(ab')2 antivenom product with an immunoglobulin content of ~80%. PCA V cross-reactivity was moderate toward venoms of major cobra species in Asia and short-neurotoxins from selected Asian species. PCA V cross-reactivity toward venoms of African cobras, other phylogenetically related cobra-like species and long neurotoxins were generally low. The finding implies that N. samarensis and N. philippinensis SaNTX have unique antigenicity distinct from other cobra species, including those of Asian lineage with SaNTX-dominant venom phenotype. Together, the findings shed light on the composition and toxicity of N samarensis venom and provide insights into the use of PCA V in the treatment of N. samarensis envenoming.